2011
DOI: 10.1371/journal.pone.0020775
|View full text |Cite
|
Sign up to set email alerts
|

Protective Immunity Induced with the RTS,S/AS Vaccine Is Associated with IL-2 and TNF-α Producing Effector and Central Memory CD4+ T Cells

Abstract: A phase 2a RTS,S/AS malaria vaccine trial, conducted previously at the Walter Reed Army Institute of Research, conferred sterile immunity against a primary challenge with infectious sporozoites in 40% of the 80 subjects enrolled in the study. The frequency of Plasmodium falciparum circumsporozoite protein (CSP)-specific CD4+ T cells was significantly higher in protected subjects as compared to non-protected subjects. Intrigued by these unique vaccine-related correlates of protection, in the present study we as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
76
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 31 publications
5
76
2
Order By: Relevance
“…Selective depletion of different immune cell populations indicated that control of blood-stage infection is dependent on CD4 T cells, which can reduce parasitemia and promote host survival (3)(4)(5)(6)(7). The ability of Plasmodium-specific memory CD4 T cells to develop and be maintained in the host appears to be altered during malaria (8,9), and this phenomenon likely contributes to the lack of a long-term, sterilizing immunity.…”
mentioning
confidence: 99%
“…Selective depletion of different immune cell populations indicated that control of blood-stage infection is dependent on CD4 T cells, which can reduce parasitemia and promote host survival (3)(4)(5)(6)(7). The ability of Plasmodium-specific memory CD4 T cells to develop and be maintained in the host appears to be altered during malaria (8,9), and this phenomenon likely contributes to the lack of a long-term, sterilizing immunity.…”
mentioning
confidence: 99%
“…11 In that study, vaccine efficacy against malaria challenge was 50% with RTS,S/AS01 and 32% with RTS,S/ AS02, and significant correlations were found between protection against malaria challenge and both CS-specific antibody responses and CMI responses induced by the RTS,S vaccine. 7,11 CD4 + T cells predominantly expressed CD40L, a co-stimulatory ligand required for T cell help that also induces the differentiation of B cells, 18,19 and IL-2, a cytokine associated with memory T cells and T cell proliferation and differentiation. 20 There was also a strong association between the frequency of IL-2 producing CD4 + T cells and titers of CS-specific antibodies in the same individual, suggesting that IL-2 may contribute to protection by promoting both cellular and humoral responses.…”
Section: Discussionmentioning
confidence: 99%
“…20 There was also a strong association between the frequency of IL-2 producing CD4 + T cells and titers of CS-specific antibodies in the same individual, suggesting that IL-2 may contribute to protection by promoting both cellular and humoral responses. 7 Methods available at the time of the study, however, did not allow for a phenotypic analysis of the CS CD4 + T cell data. Induction of CD4 + T cells directed against P. falciparum CS protein by RTS,S adjuvanted formulations has been shown in clinical field trials in adults and children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations